The handbook of interior architecture and design - Brooker, Graeme; Weinthal, Lois (Bloomsbury Academic, 2013)
The Handbook of Interior Architecture and Design offers a compelling collection of original essays that seek to examine the shifting role of interior architecture and interior design, and their importance and meaning within the contemporary world. Interior architecture and interior design are disciplines that span a complexity of ideas, ranging from human behaviour and anthropology to history and the technology of the future. Approaches to designing the interior are in a constant state of flux, reflecting and adapting to the changing systems of history, culture and politics.